2021
DOI: 10.1039/d1fo00127b
|View full text |Cite
|
Sign up to set email alerts
|

Broad-spectrum pharmacological activity of Australian propolis and metabolomic-driven identification of marker metabolites of propolis samples from three continents

Abstract: Propolis is a by-product of honeybee farming known for its broad therapeutic benefits around the world and extensively used in the health food and beverage industry. Despite Australia being one...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 111 publications
1
21
0
Order By: Relevance
“…We recently evaluated the AP-1 for the potential marker metabolites compared to Chinese and Brazilian propolis samples. In addition, seven common phenolics, including CAPE, artepillin C, galangin, chrysin, pinocembrin, daidzein and naringenin, were quantified in AP-1 using HPLC [49]. In the present study, almost no cell death was observed for normal macrophages (RAW 264.7) upon treatment with AP-1 and its DOX combination up to 200 µg mL −1 .…”
Section: Biochemometric and Lcms Metabolomic Identification Of Cytotoxic Metabolites Of Ap-1mentioning
confidence: 46%
See 4 more Smart Citations
“…We recently evaluated the AP-1 for the potential marker metabolites compared to Chinese and Brazilian propolis samples. In addition, seven common phenolics, including CAPE, artepillin C, galangin, chrysin, pinocembrin, daidzein and naringenin, were quantified in AP-1 using HPLC [49]. In the present study, almost no cell death was observed for normal macrophages (RAW 264.7) upon treatment with AP-1 and its DOX combination up to 200 µg mL −1 .…”
Section: Biochemometric and Lcms Metabolomic Identification Of Cytotoxic Metabolites Of Ap-1mentioning
confidence: 46%
“…Previously, upregulation of p-53 was reported in the MCF7 cells after treatment with Chinese [128] and Turkish propolis [129]. Our recent study showed the discriminatory metabolites of AP-1 vs. Chinese and Brazilian samples, indicating a greater antiproliferative effect of AP-1 against the MCF7 and MDA-M-B231 cells [49]. The discrepancies in the underlying cytotoxic mechanisms may be correlated to different key metabolites in the propolis samples, accounting for their differential effects on p53 expression.…”
Section: Apoptotic Proteome Profiler Array Analysis 251 Effects Of Ap-1 and Dox On Apoptotic Proteins Of The Mcf7 Cellsmentioning
confidence: 50%
See 3 more Smart Citations